Ανέκδοτος κανόνας στον Άγιο Νικόλαο επίσκοπο Μύρων της Λυκίας από τον πατριάρχη Κωνσταντινουπόλεως Γερμανό Α΄ τον ομολογητή (ca 650-740) - ΣΟΥΡΜΠΑ, ΜΑΡΙΑ (Byzantina Symmeikta, 2023)
The present study presents the first critical edition of an unedited canon on St Nicholas of Myra in Lycia composed most likely by Germanos I, Patriarch of Constantinople. The text is transmitted by three codices (Sinait. gr. 583, Sinait. gr. 590, and Athous, Lavrae Η 94), and the editio princeps of the above-mentioned canon is accompanied by a detailed study of various aspects of the text, including its manuscript tradition, structure, content and metre.